Milkfish (Chanos Chanos) Gelatin as Biosensor Material for Chromium (III) Detection - P.H. Hutapea, T; ., Rukisah; ., Mulyadi; A. Madurani, K; ., Suprapto; Kurniawan, F. (International Journal of Engineering and Technology, 2019)
Milkfish (Chanos chanos) gelatin was successfully developed as biosensor material. The milkfish bone was obtained from local restaurants in Tarakan, North Borneo, Indonesia. Gelatin was extracted from milkfish bone using acid method at 55Â°C. Characterization by FTIR showed that milkfish gelatin had similar functional group with commercial gelatin. The gelatin was used as biosensor material for detecting chromium. The gelatin was mixed with carbon in 1:1 ratio to form gelatin/carbon paste modified silver electrode. Electrochemical impedance spectroscopy (EIS) analysis of the gelatin/carbon paste modified silver electrode showed a better conductivity than paraffin/carbon paste modified silver electrode. Performance of the gelatin/carbon paste modified silver electrode in chromium (III) solution was conducted using cyclic voltammetry technique. Measurement was carried out at -1 V to +1 V with scan rate of 100 mV/s in acid and base condition. The best result was shown by gelatin/carbon paste modified silver electrode. It can detect chromium (III) ions at reduction potential of -0.78 V in alkaline condition. Unspecific responses were observed from silver electrode, paraffin/silver electrode, carbon/silver electrode, gelatin/silver electrode and paraffin/carbon paste modified silver electrode. This result can be concluded that the milkfish gelatin obtained have a potential to be developed as chromium (III) biosensor.Â Â